2018
DOI: 10.3389/fphys.2018.01405
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Oxidant/Antioxidant Status in Chronic Temporomandibular Disorders Is Dependent on Source and Intensity of Pain – A Pilot Study

Abstract: Temporomandibular disorders (TMD) have been associated with altered salivary oxidative status, but the relation with pain source and pain severity isn’t clarified. With the aim to assess their interaction with TMD, we compared levels of selected salivary oxidative stress (OS) markers (glutathione peroxidase, superoxide dismutase, total antioxidant capacity (TAC), uric acid, 8-hydroxydeoxyguanosine, malondialdehyde) and salivary cortisol (SC) as a stress indicator, between 20 TMD patients and 15 healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Within-group analyses showed a significant decrease in TAC and UA in the SS group. Our previous study on OS indicators in chronic TMD 40 showed that TAC was significantly higher in TMD patients than in healthy controls. We suggested that higher TAC in patients with TMD pain lasting more than 6 months might imply a compensatory increase of the antioxidant enzymes in response to changing levels of OS as a prerequisite for efficient defense.…”
Section: Discussionmentioning
confidence: 88%
“…Within-group analyses showed a significant decrease in TAC and UA in the SS group. Our previous study on OS indicators in chronic TMD 40 showed that TAC was significantly higher in TMD patients than in healthy controls. We suggested that higher TAC in patients with TMD pain lasting more than 6 months might imply a compensatory increase of the antioxidant enzymes in response to changing levels of OS as a prerequisite for efficient defense.…”
Section: Discussionmentioning
confidence: 88%
“…The main reason for these differences may be that in our research, we chose only female patients with chronic pain lasting 6 months or more. This six-month period provided an opportunity for the patients to adjust to potentially high oxidant levels, resulting in higher TAC levels [18]. Similar opposing results, where researchers observed higher or lower levels of TAC, have been found in other pathologies as well (e.g., atherosclerosis) [32, 33].…”
Section: Discussionmentioning
confidence: 91%
“…When it comes to TAC levels in various diseases, data are inconsistent. Research addressing oxidative status in TMD patients is scarce [17, 18, 2931], and to the best of our knowledge, no study has attempted to track changes in OS biomarker levels during TMD therapy. Rodriguez de Sotillo et al and De Almeida and Amenábar found that TAC levels were lower in the TMD group than in control groups, indicating reduced antioxidant protection [17, 31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations